Effect of weaning age on intestinal mucosal morphology, permeability, gene expression of tight junction proteins, cytokines and secretory IgA in Wuzhishan mini piglets. Issue 4 (2nd October 2018) - Xun, Wenjuan; Shi, Liguang; Zhou, Hanlin; Hou, Guanyu; Cao, Ting
Abstract: To evaluate the effects of weaning age on intestinal mucosal morphology, expressions of tight junction proteins and inflammatory cytokines, as well as secretory IgA (sIgA) of Wuzhishan piglets, a total of 96 piglets at 1-day old with an average body weight of 0.56 ± 0.07 kg were randomly divided into four treatments with four replicates per treatment and 6 pigs per replicate. Piglets in those four treatments were weaned at the age of 21(21W), 28(28W), 35 (35W) and 42 (42W) days, respectively. Blood sample was collected for determining plasma diamine oxidase (DAO) and D-lactate at 28, 35, 42, 49 and 56 days old. The jejunum and ileum segments were collected for morphology analysis, and mucosa samples were collected for Real-time PCR and sIgA measurements at 56 days old. The results showed that: compared with the 21W groups, piglets in 35W and 42W groups significantly decreased DAO activity and D-lactate level at 28 to 35 days and 56 days old ( p  < .05), increased mRNA levels of occludin and zonula occluden-1 (ZO-1) in jejunal and ileal mucosa ( p  < .05) and claudin in ileal mucosa ( p  < .05) and reduced the sIgA contents in jejunum and ileum ( p  < .05) at 56 days old. By contrary, the intestinal mucosal morphology and mRNA levels of cytokines in jejuna and ileal mucosa at 56 days old were not significantly different among the treatments ( p  > .05). Results suggest that weaning at 35 or 42 days old may be beneficial to intestinal barrier function, whereas weaning at 21 days old promoted sIgA expression.